Energy and exergy metrics analyses of Hybrid Photovoltaic-Thermal air collector. (29th July 2009) - Tiwari, Arvind; Sandhu, G.S.; Barnwal, P.; Sodha, M.S.
This paper presents the Energy Pay Back Time (EPBT) of Hybrid Photovoltaic-Thermal (HPVT) air collector based on exergy analysis for composite climate of New Delhi. The exergy metrics namely Electricity Production Factor and Life Cycle Conversion Efficiency in addition to EPBT have also been evaluated by using exergetic output. It has been observed that EPBT of HPVT air collector without balance of system based on exergy and energy output is about 10 years and 2 years, respectively, for single fan operation of the HPVT air collector. The pay back period from economic point of view has also been carried out.